Submolecular-scale control of phototautomerization - Rosławska, Anna; Kaiser, Katharina; Romeo, Michelangelo; Devaux, Eloïse; Scheurer, Fabrice; Berciaud, Stéphane; Neuman, Tomáš; Schull, Guillaume (Nature nanotechnology, 2024)
Optically activated reactions initiate biological processes such as photosynthesis or vision, but can also control polymerization, catalysis or energy conversion. Methods relying on the manipulation of light at macroscopic and mesoscopic scales are used to control on-surface photochemistry, but do not offer atomic-scale control. Here we take advantage of the confinement of the electromagnetic field at the apex of a scanning tunnelling microscope tip to drive the phototautomerization of a free-base phthalocyanine with submolecular precision. We can control the reaction rate and the relative tautomer population through a change in the laser excitation wavelength or through the tip position. Atomically resolved tip-enhanced photoluminescence spectroscopy and hyperspectral mapping unravel an excited-state mediated process, which is quantitatively supported by a comprehensive theoretical model combining ab initio calculations with a parametric open-quantum-system approach. Our experimental strategy may allow insights in other photochemical reactions and proof useful to control complex on-surface reactions.